SEBARAN DAN RESPON KETAHANAN LIMA KULTIVAR BENGKUANG (Pachyrhizus erosus (L.) Urban ) TERHADAP PENYAKIT MOSAIK - Tri Asmira Damayanti (Agrovigor, 2010)
The objective of this experiment was to investigate the yam bean mosaic disease spread in the fields (Bogor, Jawa Barat dan Prembun, Jawa Tengah) and to study the response of five yam bean cultivars against a mosaic disease. The cultivars were Wulung, Porselen, Kapas, Hideung and Paris. Plants were inoculated by viruliferous Aphis craccivora at 14 days after seedling. The incubation period, viral accumulation, disease incidence and severity were observed. The results showed that the mosaic disease distributes in all surveyed yam bean fields in Bogor and Prembun with incidence ranged from 14.2-100%. RT-PCR detection of the virus by using a pair of universal primer for Potyvirus was positively amplified a 1.7 kb DNA fragment, suggested the identity of the virus as a member of Potyvirus. Based on incubation periods, severity, and viral accumulation showed that cultivar from central Java is tolerant, while others are susceptible against the mosaic disease.